2009
DOI: 10.1016/s0140-6736(09)61034-5
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and cause-specific mortality in Russia: a retrospective case–control study of 48 557 adult deaths

Abstract: SummaryBackgroundAlcohol is an important determinant of the high and fluctuating adult mortality rates in Russia, but cause-specific detail is lacking. Our case–control study investigated the effects of alcohol consumption on male and female cause-specific mortality.MethodsIn three Russian industrial cities with typical 1990s mortality patterns (Tomsk, Barnaul, Biysk), the addresses of 60 416 residents who had died at ages 15–74 years in 1990–2001 were visited in 2001–05. Family members were present for 50 066… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
246
5
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(287 citation statements)
references
References 28 publications
21
246
5
11
Order By: Relevance
“…In the most recent CRAs, this was solved as follows 22, 267:

For hypertensive heart disease, ischaemic heart disease and both stroke types, the risk relations are specified for fatal and non‐fatal outcomes. Moreover, for ischaemic diseases, we used age‐specific risk relations 268.

For countries in eastern Europe (Russia and surrounding countries with similar drinking patterns), different relative risk estimates were used (269, based on 270). In particular, no beneficial effect was modelled because of detrimental drinking patterns and higher relative risk per heavy drinking occasion, as the average quantity per heavy drinking occasion in these countries is higher (see 41, 271, 272, 273 as background).
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the most recent CRAs, this was solved as follows 22, 267:

For hypertensive heart disease, ischaemic heart disease and both stroke types, the risk relations are specified for fatal and non‐fatal outcomes. Moreover, for ischaemic diseases, we used age‐specific risk relations 268.

For countries in eastern Europe (Russia and surrounding countries with similar drinking patterns), different relative risk estimates were used (269, based on 270). In particular, no beneficial effect was modelled because of detrimental drinking patterns and higher relative risk per heavy drinking occasion, as the average quantity per heavy drinking occasion in these countries is higher (see 41, 271, 272, 273 as background).
…”
Section: Resultsmentioning
confidence: 99%
“…For countries in eastern Europe (Russia and surrounding countries with similar drinking patterns), different relative risk estimates were used (269, based on 270). In particular, no beneficial effect was modelled because of detrimental drinking patterns and higher relative risk per heavy drinking occasion, as the average quantity per heavy drinking occasion in these countries is higher (see 41, 271, 272, 273 as background).…”
Section: Resultsmentioning
confidence: 99%
“…В период с 1991 по 2000 г. число злоупотребля-ющих алкоголем подростков, находившихся под наблю-дением наркологов, увеличилось на 23,6% [29]. Среди всех случаев смерти в возрасте 15-54 лет, проанализирован-ных ретроспективно в большом кооперативном исследо-вании, проводившемся в России, 52% связаны с приемом АН [30]. По данным обследования студентов двух меди-цинских вузов Воронежа и Ростова, в котором приняли участие студенты I и VI курсов [31], употребление алкого-ля среди студентов-старшекурсников по степени выра-женности значительно выше, чем у студентов I курса.…”
Section: результаты и обсуждениеunclassified
“…This situation is similar to that observed in 1998 and 1999 by Gazal-Carvalho et al 25 in the city of São Paulo. In Russia, a casecontrol study involving almost 50,000 deaths showed a risk approximately 6 times higher of deaths by accidents and violence in the group that presented high alcohol consumption, besides the risk for other diseases, especially chronic 26 .…”
Section: * Percentual Ajustado Para Representar a População Adulta Tomentioning
confidence: 99%